Peran Love of Money, Financial Attitude, dan Financial Self-Efficacy terhadap Pengelolaan Keuangan Mahasiswa yang Berwirausaha di Kota Semarang - Monica Dwi Handayani; Diana Puspitasari; Dian Prawitasari; Fakhmi Zakaria (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The growth of student entrepreneurship in Semarang City has not been fully accompanied by adequate financial management capabilities. Financial record-keeping problems, particularly the inability to separate personal and business finances, remain prevalent and tend to increase, potentially hindering the sustainability of student-owned MSMEs.  This study aims to examine the effects of Financial Attitude, Financial Self-Efficacy, and Love of Money on the financial management of student entrepreneurs in Semarang City. A quantitative approach with a survey method was employed, involving 182 student entrepreneurs selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with Structural Equation Modeling–Partial Least Square (SEM-PLS) using SmartPLS 4. The results indicate that Financial Attitude, Financial Self-Efficacy, and Love of Money have a positive and significant effect on students’ financial management. The R-square value of 0.670 demonstrates the model’s ability to explain variations in financial management. In conclusion, psychological financial factors play an important role in improving financial management among student entrepreneurs.